Purification and structural characterisation of (1 -> 3 ; 1 -> 6)-beta-D-glucans (botryosphaerans) from Botryosphaeria rhodina grown on sucrose and fructose as carbon sources: a comparative study - da Silva, MDC; Izeli, N. L.; Martinez, P. F.; Silva, I. R.; Constantino, CJL; Cardoso, M. S.; Barbosa, A. M.; Dekker, RFH; da Silva, GVJ (Elsevier B.V., 2005)
Two botryosphaerans, exopolysaccharides (EPS) secreted by the ascomyceteous fungus Botryosphaeria rhodina, when grown on sucrose and fructose as sole carbon sources, were structurally compared after their isolation from the culture medium. Both EPS were submitted to trypsin digestion, and eluted as a single peak on gel filtration. Total acid hydrolysis yielded only glucose, and data from methylation analysis and Smith degradation indicated that both EPS constituted a main chain of glucopyranosyl beta(1 -> 3) linkages substituted at O-6. The products obtained after partial acid hydrolysis demonstrated side chains consisting of glucosyl- and gentiobiosyl- linked beta(1 -> 6) residues. C-13-NMR spectroscopy studies showed that all glucosidic linkages were of the beta-configuration. The carbon source affected the side chain structures of botryosphaeran but not the main chain makeup. Sucrose produced less branching (21%) than fructose (31%). (c) 2005 Published by Elsevier Ltd.
Keywords: Botryosphaeria rhodina; exopolysaccharides; beta(1 -> 3; 1 -> 6)-D-glucans; carbon source; structural variation